A rapidly-reversible absorptive and emissive vapochromic Pt(II) pincer-based chemical sensor. Issue 1 (December 2017) - Bryant, M.; Skelton, J.; Hatcher, L.; Stubbs, C.; Madrid, E.; Pallipurath, A.; Thomas, L.; Woodall, C.; Christensen, J.; Fuertes, S.; Robinson, T.; Beavers, C.; et al.
Abstract Selective, robust and cost-effective chemical sensors for detecting small volatile-organic compounds (VOCs) have widespread applications in industry, healthcare and environmental monitoring. Here we design a Pt(II) pincer-type material with selective absorptive and emissive responses to methanol and water. The yellow anhydrous form converts reversibly on a subsecond timescale to a red hydrate in the presence of parts-per-thousand levels of atmospheric water vapour. Exposure to methanol induces a similarly-rapid and reversible colour change to a blue methanol solvate. Stable smart coatings on glass demonstrate robust switching over 104 cycles, and flexible microporous polymer membranes incorporating microcrystals of the complex show identical vapochromic behaviour. The rapid vapochromic response can be rationalised from the crystal structure, and in combination with quantum-chemical modelling, we provide a complete microscopic picture of the switching mechanism. We discuss how this multiscale design approach can be used to obtain new compounds with tailored VOC selectivity and spectral responses. Solid state Pt(II)-pincer complexes exhibiting vapochromic responses show promise for chemical sensing applications, but their slow responses typically limit their utility. Here, Raithby and colleagues design a Pt(II)-pincer complex with a subsecond, highly-selective vapochromic response to water and methanol.